Analisis Faktor-Faktor yang Berpengaruh terhadap Produktivitas Kerja Pegawai pada BPMPD Provinsi Sulawesi Barat - Quraisy, Hasbullah (Patria Artha Management Journal, 2017)
Development of human resources (HR) aim to improve the quality of professionalism and skills of civil servants in carrying out its duties and functions optimally is deemed to be lacking in the Community Empowerment Board and Village Government ( BPMPD ) .Sumber human power is determined by their competence, motivation and discipline work that should be owned by every employee , so the aim of this research to know the competence , motivation and discipline of work which is owned by the employees of Community Empowerment Board and Village Government of West Sulawesi province .Based on the results of the analysis outputs simultaneous test (Test F) note that the value of F 21,757 and F table 2.79, in this case if the value of F count > F table with significant value 0,000 less than the value α of 0.05. So that the decisions taken are H0 and H1 accepted. That is competence (X1) motivation (X2) and discipline (X3) together or simultaneously significant effect on employee productivity, the partial test results showed tcount for variable competences of the employees in the work of 4,296 larger when compared to the value ttabel 1.67 and significant value of 0.000 which is smaller than the value of alpha (α) 0.05 (5%) or can be viewed 0.000 < 0.05 hence H0 refused and H1 accepted, tcount for variable employee motivation in the work amounted to 2,899 larger when compared to the value ttabel 1.67 and 0.021 significant value which is greater than the value of alpha (α) 0.05 (5%) or can be viewed 0.21< 0.05 hence H0 refused and H1 accepted and H1 refused and tcount for variable 2,497 employees work discipline is greater when compared with the value of 1.67 ttabel and significant value of 0.015 which is smaller than the value of alpha (α) 0.05 (5%) or can be viewed 0.015 < 0.05 hence H0 and H1 accepted. Results of the analysis showed the output of work discipline variable most dominant influence on the increase in employee productivity in the Community Empowerment Board and Village Government (BPMPD) West Sulawesi province. Keywords: Work Productivity; Competence; Motivation; and Work Discipline.